Building Telephony System with Asterisk: an easy introduction to using and configuring Asterisk to build feature-rich telephony systems for small and medium businesses - Gomillon, David (Packt Publishing, 2005)
Provides an introduction to using and configuring Asterisk to build feature-rich telephony systems for small and medium businesses. This book takes you step-by-step through the process of installing and configuring Asterisk. It shows you how to make a deployment plan, and how to create a dial plan.